KEEFEKTIFAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK LATIHAN ASERTIF UNTUK MENINGKATKAN KOMUNIKASI INTERPERSONAL PESERTA DIDIK KELAS IX SMP NEGERI 5 PONTIANAK - Andini Putri; Muhammad Asrori; Halida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to test the effectiveness of group counseling services using assertiveness training techniques to improve students’ interpersonal communication at SMP Negeri 5 in Pontianak. This study employed an experimental method with a pre-experimental design, specifically a one-group pretest-posttest design. The data collection technique used was the Interpersonal Communication Inventory. Data analysis was conducted using the parametric Paired Sample T-Test. The results showed that students’ pretest scores had an average percentage of 44.25%, falling into the low category, while their posttest scores had an average percentage of 72%, falling into the high category, representing an increase of 27.75%. The results of the hypothesis test showed that the t-value was -12.511 with a significance level of 0.000 < 0.05, which means that H0 was rejected and Ha was accepted. Thus, it can be concluded that there was a significant improvement after group counseling using assertiveness training techniques to enhance the interpersonal communication skills of students at SMP Negeri 5 in Pontianak.